A factor analytic examination of women's and men's friendship preferences. (May 2023) - Ayers, Jessica D.; Krems, Jaimie Arona; Aktipis, Athena
Abstract: Friendships are valuable relationships that can bestow many benefits. How can humans ensure they receive the maximum benefits with minimal potential costs? One possible solution is to have preferences for traits, expectations, and rules in friendship. This could, for example, help people pursue beneficial friendships and jettison costly friendships. Previous research robustly documented that such preferences for traits, expectations, and rules exist, though they are often combined, and indicates that these preferences may be sex-specific. Across two studies ( N  = 853), our factor analyses documented that preferences for desired traits in friendship are organized into two broad categories with women rating intrinsic traits as more important in their friendship compared to men's ratings. Similarly, factor analyses showed that preferences for rules in friendship are organized into four broad categories with women rating all rule categories as more important in their friendships compared to men's ratings. Highlights: Previous research often combines friendship preferences across investigations. We used factor analyses to investigate the underlying structure of preferences. We found that preferences for traits grouped into two broad categories. We found that preferences for rules grouped into four broad categories. We found sex differences in these preferences that align with previous research.